The Effect of Discounts and Sales Promotion on Shopee Users Repurchase Intention with Customer Satisfaction as a Moderating Variable - Ari Soeti Yani; Isma Maisarah (IJHCM (International Journal of Human Capital Management), 2023)
This study aims to test and analyze the effect of discounts and sales promotion on repurchase intention with customer satisfaction as a moderating variable. The population in this study used a sample of 344 respondents who were users of the Shopee application aged 18-28 years. The data collection technique uses simple random sampling by spreading research questionnaires in the form of google forms through social media. The data processing method in this study is to use smartPLS with the aim of testing hypotheses. The results of this study show that discount has a positive and significant effect on repurchase intention, sales promotion has a positive and significant effect on repurchase intention, customer satisfaction has a positive and significant effect on repurchase intention, customer satisfaction is significant and can moderate the effect of discount on repurchase intention, customer satisfaction has a significant effect on repurchase intention and can moderate the effect of sales promotion on repurchase intention. The results of this study recommend to Shopee, if you want to increase consumer repurchase interest, it is necessary to provide more attractive discounts and sales promotions in the form of free shipping which must continue to be applied so as to increase customer satisfaction and make consumers will return to shopping.